PERLINDUNGAN HUKUM EKSPRESI BUDAYA TRADISIONAL PERMAINAN MEGANDU DI DESA ADAT OLE KABUPATEN TABANAN - Gunadi, K.M.; Putra, I.P.R.A. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
The purpose of this service is to create a law-aware society and build awareness about the importance of legal protection for the Traditional Cultural Expression of the Megandu game in the Ole Traditional Village. The game Megandu as a copyrighted work has been played for generations by the indigenous Ole community and has even become a village icon. The megandu game, which once represented the Tabanan district at the Bali Arts Festival, really needs to be given legal protection. The target of this service is to focus on all elements of society, especially art activists in the Indigenous Village of Ole, because art activists and all elements of society really need to understand the importance of legal protection of a work created by the community which has become a cultural heritage from generation to generation as an expression of traditional culture. . The results achieved in this service are raising public legal awareness to register their copyrighted works to avoid claims from irresponsible parties. Registering the Megandu game and coaching the procedure for registration through the direct lecture method is the most important part of this community service activity. The implementation of community service activities was greeted with great enthusiasm, with the existence of legal awareness from the community regarding legal protection for their copyrighted works it will be very easy to follow up on efforts to realize a legal protection for copyrighted works as stipulated in Law Number 28 of 2014 concerning Copyright. Keywords: Socialization, Legal Protection, Traditional Cultural